Role of catechol siderophore synthesis in Vibrio vulnificus virulence. - Litwin, C M (1996)
We isolated a Vibrio vulnificus TnphoA mutant that was unable to produce catechol siderophores or to acquire iron from transferrin. This mutant showed reduced virulence in an infant mouse model. The TnphoA insertion was in an open reading frame designated venB. The venB gene cloned on a plasmid restored catechol production to the mutant. The deduced amino acid sequence of venB is 41% identical to the enzyme isochorismatase of Escherichia coli (EntB), an enzyme involved in the biosynthesis of the catechol siderophore enterobactin.